2020
DOI: 10.1371/journal.pone.0243415
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for the interviewing process during Coronavirus disease-19 pandemic: Virtual interviewing experiences of applicants and interviewers, a systematic review

Abstract: Purpose Coronavirus disease-19 (COVID-19) has forced upon all academic institutions to conduct virtual interviewing (VI) instead of face-to-face interviewing (FTFI) this interviewing cycle. The purpose of this systematic review was to understand the process of VI, its effectiveness as an alternative to FTFI, and the experiences of applicants and institutions with VI. We also share best practice strategies for applicants and institutions in VI preparation. Method PubMed/MEDLINE, Cochrane Library of Systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 24 publications
(159 reference statements)
0
31
0
Order By: Relevance
“… 21 Generally, a large proportion of applicants and interviewers reported satisfaction with their ability to convey themselves adequately during the virtual interviews. 9 However, both groups reported limited personal interactions during virtual-only interviews as a notable downside. 4 , 7 Following the fellowship interviews, programs felt that virtual interviews limit the applicants’ ability to appreciate the training program's culture or the atmosphere of the training program and hospital.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 21 Generally, a large proportion of applicants and interviewers reported satisfaction with their ability to convey themselves adequately during the virtual interviews. 9 However, both groups reported limited personal interactions during virtual-only interviews as a notable downside. 4 , 7 Following the fellowship interviews, programs felt that virtual interviews limit the applicants’ ability to appreciate the training program's culture or the atmosphere of the training program and hospital.…”
Section: Discussionmentioning
confidence: 99%
“…The more likely outcome from the insight gained from the virtual-only interview format would be moving towards a hybrid model of virtual and in-person interviews. Studies prior to the COVID-19 pandemic concluded that applicants and interviewers have hesitation with virtual interviews replacing in-person interviews 9 ; however many concluded that virtual interviews may be an effective adjunct to screen applicants prior to in-person interviews. 9 , 11 , 17 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recently published systematic review article about preparing for the virtual interviewing process described virtual interviewing experiences from interviewees and interviewing institutions in healthcare and additionally shared best virtual interviewing practices for the interviewees and interviewing institutions. 2 However, it will be crucial to further explore the impact of virtual interviewing on the admission process during the pandemic. Similarly, the impact of other forced changes on medical education need to be individually explored in further depth to understand if virtual learning has negatively impacted medical student education.…”
mentioning
confidence: 99%